Pengaruh Kecerdasan Emosional, Kemandirian Belajar, Gaya Belajar, Dukungan Orang Tua, Dan Lingkungan Belajar Terhadap Prestasi Belajar Akuntansi Pada Siswa Kelas X Smk Negeri 4 Sijunjung - Basir, Nesri Susanti; Jolianis, Jolianis; Syahrul, Alfattory Rheza (Jurnal Horizon Pendidikan, 2022)
This study aims to analyze 1) the influence of emotional intelligence on learning achievement, 2) the influence of student learning independence partially on learning achievement, 3) the influence of learning styles on learning achievement, 4) the influence of parental support on learning achievement, 5) the influence of the learning environment on learning achievement, (6) the influence of emotional intelligence, learning independence, learning styles, parental support and the learning environment stimultan on achievement study accounting in class X students of SMK Negeri 4 Sijunjung. This type of research is descriptive and associative research. The population in the study was all class X students of SMK Negeri 4 Sijunjung for the 2021/2022 school year, totaling 72 people. The sample was 51 people with a sampling technique in the form of a stratified random sampling technique based on the income level of the parents of the students. The instruments used for this study were in the form of a closed questionnaire with the use> of the Multilevel Multiple Linear Regression test and the hypothesis test with the t test and the F test. ttable of 2,014; (2) there is a significant influence between learning independence on learning achievement with a regression coefficient value of 0.297, a calculated value of 3.485>ttabel of 2.014; (3) there was a significant influence of learning style on learning achievement with a regression coefficient value of 0.235, a calculated value of 2.934>ttabel of 2.014; (4) there is a significant influence of parental support on learning achievement with a regression coefficient value of 0.374 and a calculated value of 4.250>ttabel of 2.014; (5) there is a significant influence of the learning environment on learning achievement with a regression coefficient value of 0.234 and a calculated value of 2.990>ttabel of 2.014; (6) there is a significant influence between emotional intelligence, learning independence, learning styles, parental support and a stimultan learning environment on learning achievement with a calculation of 104,929>Ftabel 2.57.Keywords: Emotional Intelligence, Learning Independence, Learning Styles, Parental Support, Learning Environment, And Learning Achievement